Efficacy and Mechanism of Antibiotic Degradation by Oxidantion - Porada, Lisa; Donohoe, Mika; Beckham, Brenna; Doge, Jack; Mayer, Zulkefly (Journal of Green Energy and Environmental Engineering, 2024)
The degradation technology of sulfonamide antibiotics (SAs) in the aquatic environment has been a hot topic in recent years, and Advanced Oxidation Processes (AOPs) have achieved rapid progress in both fundamental mechanistic studies and practical applications. This study employs a liquid-phase impregnation method to modify zero-valent iron (Fe⁰) using the common aminopolycarboxylic acid (APCA) chelating agent EDTA, constructing an EDTA-Fe⁰/Peracetic Acid (PAA) catalytic system. Using the typical antibiotic sulfamethazine (SMT) as the target pollutant, the influence of modification parameters, reaction system dosage, initial pH, and coexisting anions was investigated, aiming to reveal the enhanced activation mechanism of EDTA-Fe⁰ within the system.